2020
DOI: 10.1080/00949655.2020.1836184
|View full text |Cite
|
Sign up to set email alerts
|

Statistical properties of Poisson-Voronoi tessellation cells in bounded regions

Abstract: Many spatial statistics methods require neighbourhood structures such as the one determined by a Voronoi tessellation, so understanding statistical properties of Voronoi cells is crucial. While distributions of cell properties when data locations follow an unbounded homogeneous Poisson process have been studied, little attention has been given to how these properties change when a boundary is imposed. This is important when geographical data are gathered within a restricted study area, such as a national bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…S2), which should depend only on the area and be independent of the perimeter. Thus, the λ P -independence of µ validates the phenomenological implementation [57,58] of this constraint. Second, these results can provide crucial insights regarding the model parameters.…”
Section: Comparison With Simulationssupporting
confidence: 64%
See 1 more Smart Citation
“…S2), which should depend only on the area and be independent of the perimeter. Thus, the λ P -independence of µ validates the phenomenological implementation [57,58] of this constraint. Second, these results can provide crucial insights regarding the model parameters.…”
Section: Comparison With Simulationssupporting
confidence: 64%
“…S2), Eq. ( 6), together with the constraint of confluency [57,58], give the distribution for the scaled area a = A/Ā, whereĀ is the average of area, A. It is a Gamma distribution, with a single parameter µ,…”
Section: Analytical Theory For the Shape Variabilitymentioning
confidence: 99%
“…Additionally, as detailed in ‘Distribution for area’, Equation 18 together with the constraint of confluency ( Weaire, 1986 ; Gezer et al, 2021 ), give the distribution for the scaled area , where is the average of area. It is a Gamma distribution, with a single parameter μ, …”
Section: Resultsmentioning
confidence: 99%
“…In particular Koufos and Dettmann (2019) considered PV cells located close to the boundaries of the quadrant R + and obtained that the gamma distribution, with location-dependent parameters, provides a reasonably good approximation to the distribution of cell area. Gezer et al (2021) compared the statistical properties of the area of PV cells in the infinite plane and of clipped cells in two bounded regions: the unit square and the convex hull of the points; they found that the generalized gamma distribution provides a good fit with parameters varying according to the location of the cell seed in the bounded region. It should be noted that, as the number of the points increases, the vast majority of cells are not affected by the imposition of boundaries; indeed Devroye et al (2017) have shown that the asymptotic distribution of the Voronoi cell area is independent of the location of the seed and of the intensity measure underlying the Poisson point process.…”
Section: Introductionmentioning
confidence: 99%